Strangulated bowel obstruction caused by an ileo-ileal knot: a rare case report - Satoko Umetsu; Shigeru Shibata; Harue Akasaka; Shinji Tsutsumi; Chiaki Uchida; Hirokazu Ogasawara (Surgical Case Reports)
Abstract Background Intestinal knot formation is a condition wherein two segments of the intestine are knotted together; however, reports of small-intestinal ileo-ileal knot formation are rare. Case presentation The patient was a 62-year-old Asian male with a history of endoscopic colorectal adenoma resection and a spontaneous pneumothorax. The patient had no history of a laparotomy. He consulted his local doctor with the chief complaint of abdominal pain and was admitted to our hospital with suspicion of an acute abdomen. The abdomen had muscular guarding with tenderness and rebound tenderness. Contrast-enhanced computed tomography (CT) showed torsion of the mesentery of the small intestine with poor contrast filling. The patient was referred to our department with strangulated bowel obstruction and underwent an emergency laparotomy. Intraoperative findings revealed that two segments of the ileum were wrapped around each other to form a knot, and the strangulated small bowel was necrotic. After the release of the knot, partial resection of the small intestine was performed from 220 cm distal to the ligament of Treitz to 80 cm proximal to the cecum. The patient had a good postoperative course and was discharged on the 11th postoperative day. Conclusion Ileo-ileal knots should be considered as part of the differential diagnosis when treating strangulated bowel obstruction.